Data driven stochastic modelling and simulation of cooling demand within breweries - Hubert, Stefan; Helmers, Thorben; Groß, Frauke; Delgado, Antonio (Journal of Food Engineering, 2016)
Over the last few decades the food and beverage industry has become increasingly aware of its energy and water usage. Customers are demanding an increasing level of sustainability. This is especially true within the brewery industry. The process of brewing itself is a demanding process, with respect to both energy and water requirements. To increase the knowledge about the holistic process chains, e.g. for decision making and for testing operational and procedural setups there is an evolving need for virtualisation. This paper focuses on modelling and simulation of parts within the process of brewing. The shown approach utilises reference nets as a flow-chart-like modelling environment. Models based on the Java programming language are implemented, dealing with stochastic and deterministic events. Results of eight different brew types are shown and a complete schedule with a total of 230 batches, portraying almost a year of production is being simulated.
UnivIS-Import:2015-10-26:Pub.2015.tech.ITC.stmmec.datadr
Keywords: Brewery; Energy demand; Reference nets; Simulation; Stochastic modelling; Uncertainty

Hybrid plant-wide Simulation and Modelling using Reference nets and Java - Hubert, Stefan; Rückert, Darius; Delgado, Antonio (Elsevier B.V., 2016)
Keywords: hybrid; petri nets; java; reference nets; plant-wide; simulation and modelling

Implementation of dynamic biological process models into a reference net simulation environment - Pettigrew, Liam; Hubert, Stefan; Groß, Frauke; Delgado, Antonio (Simulation in Production and Logistics, 2015)
UnivIS-Import:2018-02-22:Pub.2015.tech.ITC.stmmec.implem

Optimisation of water usage in a brewery clean-in-place system using reference nets - Pettigrew, Liam; Blomenhofer, Verena; Hubert, Stefan; Groß, Frauke; Delgado, Antonio (Journal of Cleaner Production, 2015)
The brewery industry is becoming increasingly aware of its water and energy usage due to stricter regulations, and environmental and economic incentives. An area where large improvements in water usage presents itself is the clean-in-place system. A significant portion of the total process water required in an industrial sized brewery is used during clean-in-place processes. Testing and optimisation of these industrial processes can be quickly and economically achieved using computer modelling and simulation tools. One such tool is the reference net, a subclass of object-oriented Petri nets. In order to predict the water usage and the potential for energy production from wastewater attributed to the clean-in-place plant in a brewery, the reference net formalism is used. Validation of the complete reference net system is undertaken using two sets of simulations, one set of simulations running an approximation of a standard brewery clean-in-place system and a second set implementing a fuzzy logic adaptive control for water reuse. The reference net is found to be a valid and efficient tool for quick prototyping of new and existing industrial sized brewery clean-in-place systems.
UnivIS-Import:2015-03-09:Pub.2015.tech.ITC.stmmec.optimi
Keywords: Brewery; Clean-in-place; Fuzzy logic; Petri nets; Reference nets; Water usage

Save water and energy! - Holistic material and energy flow management of water and wastewater cyles in the food and beverage industry using the example of breweries - Hubert, Stefan; Helmers, Thorben; Mießner, Ulrich; Groß, Frauke; Delgado, Antonio (eFOOD-Lab International, 2015)
Keywords: Energy management; Water; Wastewater. Food industry; Bewerage industry

Simulation-based optimisation of wastewater flow and composition for on-site treatment in the food and beverage industry utilising reference nets in combination with genetic algorithms - Hubert, Stefan; Pettigrew, Liam; Helmers, Thorben; Mießner, Ulrich; Groß, Frauke; Räbiger, Norbert; Delgado, Antonio (Proceedings in Applied Mathematics and Mechanics, 2014)
UnivIS-Import:2015-07-08:Pub.2014.tech.ITC.stmmec.simula_4

Simulation modeling of bottling line water demand levels using reference nets and stochastic models - Hubert, Stefan; Baur, Franz; Delgado, Antonio; Helmers, Thorben; Räbiger, Norbert (WSC '15 Proceedings of the 2015 Winter Simulation Conference, 2015)
UnivIS-Import:2018-09-06:Pub.2015.tech.ITC.stmmec.simula